Algumas notas sobre religião e cultura de consumo (Some notes on religion and consumer culture) - DOI: 10.5752/P.2175-5841.2010v8n17p146 - Perez, Léa Freitas (Horizonte, 2010)
The text deals with the role of religion in contemporary society from the reflection of the relationship between the sacred and the consumer culture, a current field that refers to the classic theme of the relationship between religion and modernity. It starts with the verification of the existence in contemporary society of a diverse and broad constellation of religious expressions/modulations, from which, and in the company of Featherstone, of Derrida and Vattimo, among others, it questions the current understanding about religion, suggesting another route to understand the sacred in contemporary society, according to which the sacred is in full harmony with the spirit of the time, facilitating enjoyable, hedonistic and hybridizing experiences, because it fits in the consumer market, alongside with other significant complexes. The paper concludes bringing the idea that religion continues to act on life, being a source of meaning and experience, but not necessarily and exclusively only in the form of formal institutional and traditional religion, indicating the need, in a highly conceptual level, in order to understand in a more accurate and detailed way the contemporary culture and the place where religion fits in it, to rethink our usual culture and religion definitions, considering its epistemic grounding.